2018
DOI: 10.3390/met8050345
|View full text |Cite
|
Sign up to set email alerts
|

Valuable Metal Recycling

Abstract: As the global economy grows, demand for metal continues to increase. Unfortunately, metal resources are in limited supply [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The presence of several metals of different chemical nature in increasingly miniaturized products, and incorporated in complex matrixes encompassing ceramics, resins, plastics, and especially halogenated substances (based on chlorine and bromine) makes their recycling process quite complex. A spectrum of contributions focused on current state-of-the-art research on metal recycling from wastes was introduced in a special issue (Valuable Metal Recycling) of Metals [8]. An extensive overview for the recovery of high value metals from electronic waste and spent catalysts using improved pyrometallurgical and hydrometallurgical technologies was given by Ding et al [9].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of several metals of different chemical nature in increasingly miniaturized products, and incorporated in complex matrixes encompassing ceramics, resins, plastics, and especially halogenated substances (based on chlorine and bromine) makes their recycling process quite complex. A spectrum of contributions focused on current state-of-the-art research on metal recycling from wastes was introduced in a special issue (Valuable Metal Recycling) of Metals [8]. An extensive overview for the recovery of high value metals from electronic waste and spent catalysts using improved pyrometallurgical and hydrometallurgical technologies was given by Ding et al [9].…”
Section: Introductionmentioning
confidence: 99%
“…The results described in Part I [ 1 ] of this investigation combined with research works cited therein [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ] gave a general view of needs and secondary sources for a large range of materials, identified frequently as critical and strategic materials, and they are indispensable for present and forthcoming innovations in renewable energies, transportation and cutting-edge technologies.…”
Section: Introductionmentioning
confidence: 80%
“…As shown in Figure 18, gold, which is used in PCBs to assure circuit board contacts, seems to be inert to the treatment at this temperature. A thermodynamic calculation [39] showed that the values of the ∆ r G • for the reaction (6), (7), (8) and (9) at 500 • C are −119.80, −124.11, −143.22 and -119.97 kJ/mol HBr, respectively. Such negative values suggest that the envisaged reactions are favorable from the thermodynamic point of view.…”
Section: Preliminary Results For Treatment Of E-waste In Airmentioning
confidence: 99%
“…According to the above, there is a great potential in transforming industrial and electronic wastes in materials resources. However, recycling remains at a low level, so there is a needing to work in searching for improvements to the actual technologies applied to recover precious metals from wastes [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%